Multidimensional Poverty Analysis : Looking for a Middle Ground - Ferreira, Francisco H.G.; Lugo, Maria Ana (Published by Oxford University Press on behalf of the World Bank, 2015)
Widespread agreement that poverty is a multifaceted phenomenon encompassing deprivations in multiple dimensions clashes with the vociferous disagreement about how best to measure these deprivations. Drawing on the recent literature, this short paper reviews three methodological alternatives to the false dichotomy between scalar indices of multidimensional poverty, on the one hand, and a “dashboard” approach that considers only marginal distributions, on the other. These alternatives include simple Venn diagrams of the overlap of deprivations across dimensions, multivariate stochastic dominance analysis, and the analysis of copula functions, which capture the extent of interdependency across dimensions. Examples are provided from the literature on both developing and developed countries.